DEIKSIS DALAM CERITA RAKYAT NEGERI PARA PHUYANG HIKAYAT KOMERING PITU PHUYANG KARYA HBR. HIMAWAN BASTARI R. - Fisnia Pratami; Prillia Ekaningtiass; Mardiah Hayati (Universitas Batanghari, 2021)
Deixis in the folklore Negeri Para Phuyang Hikayat Komering Pitu Phuyang by Hbr. Himawan Bastari R. is the problem in this article. The purpose of this article is to describe the use of deixis in the folklore Negeri Para Phuyang Hikayat Komering Pitu Phuyang by Hbr. Himawan Bastari R.. Qualitative descriptive method is the method that chosen by the author in this study. Through qualitative descriptive method the writer can find data in the form of words or sentences related to deixis in the folklore of Negeri Para Phuyang Hikayat Komering Pitu Phuyang by Hbr. Himawan Bastari R.. After that the author will analyze and calssify based on the form of space deixis, time deixis, and person deixis. Based on the data analysis, it was found that the use of deixis in the folklore Negeri Para Phuyang Hikayat Komering Pitu Phuyang by Hbr. Himawan Bastari R. in the form of person deixis, space deixis, and time deixis. Person deixis are divided into three, the first person (I, -my, my-, we, us), the second person (you, you, you, you, you, sir, older brother), the third person (them). Space deixis is like the phrase here and time deixis is the word later. Keywords: Deixis, folklore, Negeri Para Phuyang Hikayat Komering Pitu Phuyang